Healthcare Associated Infections: Epidemiology, Contributing Factors and Control Measure in Developing Country - Amgain, Kapil; Rana, Tika; Shrestha, Ranish; Shrestha, Sunil (Journal of Karnali Academy of Health Sciences, 2019)
Nosocomial infection or Healthcare-associated infection (HCAI) is a type of infection that occurs in a patient while receiving care in a hospital or other health care facility, and which was not present during admission. Epidemiological data suggests such infections to be the primary adverse event in a healthcare institute, with a greater risk of occurring in developing countries like Nepal. This article intends to suggest the various factors contributing to and the methods that the healthcare workers and other stakeholders could adopt to prevent and control the infectious diseases in order to reduce the HCAI-related morbidity and mortality in developing countries such as Nepal.